ChemInform Abstract: Efficient Total Synthesis of (S)‐Dihydroresorcylide, a Bioactive Twelve‐Membered Macrolide. Issue 44 (14th October 2013) - Zhang, Li; Ma, Wenquan; Xu, Lili; Deng, Fei; Guo, Yuewei
Abstract A total synthetic approach towards the title compound (VII), a natural compound from Acremonium zeae with interesting phytotoxic activity, is presented from orcinol monohydrate and involves 9 steps.